Systematic Administration of B Vitamins Alleviates Diabetic Pain and Inhibits Associated Expression of P2X3 and TRPV1 in Dorsal Root Ganglion Neurons and Proinflammatory Cytokines in Spinal Cord in Rats - Duan-Duan He; Yu Gao; Shan Wang; Zhong Xie; Xue-Jun Song (Pain Research and Management)
Background. Treatment of diabetic neuropathic pain (DNP) continues to be a major challenge, and underlying mechanisms of DNP remain elusive. We investigated treatment effects of B vitamins on DPN- and DNP-associated alterations of neurochemical signaling in the nociceptive dorsal root ganglion (DRG) neurons and the spinal cord in rats. Methods. DNP was produced in male, adult, Sprague Dawley rats by single i.p. streptozotocin (STZ). Western blot analysis and immunohistochemistry were used to analyze protein expressions in DRG and ELISA to measure the proinflammatory cytokines in the spinal cord. Behaviorally expressed DNP was determined by measuring the sensitivity of hindpaw skin to mechanical and thermal stimulation. Results. There were 87.5% (77/88) rats which developed high blood glucose within 1-2 weeks following STZ injection. Of which, 70.13% (n = 54/77) animals exhibited DNP manifested as mechanical allodynia and/or thermal hyperalgesia. Intraperitoneal administration of vitamins B1/B6/B12 (100/100/2 mg/kg, one or multiple doses) significantly attenuated DNP without affecting the blood glucose. Expressions of P2X3 and TRPV1 in CGRP-positive and IB4-positive DRG neurons as well as the interleukin-1β, tumor necrosis factor-α, and nerve growth factor in the lumbar spinal cord were greatly increased in DNP rats. Such DNP-associated neurochemical alterations were also greatly suppressed by the B-vitamin treatment. Conclusions. B-vitamin treatment can greatly suppress chronic DNP and DNP-associated increased activities of P2X3 and TRPV1 in DRG and the spinal proinflammatory cytokines, which may contribute to the pathogenesis of DNP. Systematic administration of B vitamins can be a strategy for DNP management in clinic.